Optimizing Free Functioning Muscle Transfer for Lower Limb Reconstruction: A Biomechanical Approach - Huang, Ren-Wen; Hsu, Chung-Chen; Lin, Cheng-Hung; Lin, Chih-Hung (Seminars in Plastic Surgery, 2025)
Free functioning muscle transfer (FFMT) is widely used to reconstruct complex lower limb defects involving muscle deficits. This review explores ways to optimize FFMT outcomes by examining biomechanical considerations, particularly balancing the needs for stable joint positioning (isometric function) and active motion (isotonic function) for specific reconstructive objectives. We discuss knee extension, ankle dorsiflexion, and ankle plantarflexion reconstruction, recommending suitable donor muscles based on their mechanical properties and functional requirements. Important considerations include careful donor muscle selection, accurate muscle tensioning during surgery, secure tendon attachment methods, and targeted rehabilitation timed with nerve recovery. This approach offers practical advice for surgeons aiming to restore movement and improve overall function in patients undergoing complex lower limb reconstructions.
Keywords: free functioning muscle transfer; lower extremity reconstruction; functional outcomes; donor muscle selection